2017
DOI: 10.4067/s0718-95162017000300011
|View full text |Cite
|
Sign up to set email alerts
|

Yield and nitrogen use efficiency of rice-wheat cropping system in gypsum amended saline-sodic soil

Abstract: It is critical to determine nitrogen use efficiency (NUE) to find to which extent higher rates of nitrogen can improve crop yield with effective management practices. Two-year field experiments were conducted to investigate yield and NUE of rice-wheat cropping system on saline-sodic soil. Treatments included were two nitrogen (N) application rates, i.e. 15% (N 115 ) and 30% (N 130 ) higher than the recommended rates for normal soil, along with gypsum at the rates of 50% (SGR 50 ) and 100% (SGR 100 ) of soil gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
(17 reference statements)
1
10
0
3
Order By: Relevance
“…In calcareous soils, characterized by alkaline or sub-alkaline pH, the presence of calcium carbonate (CaCO 3 ) and bicarbonate (HCO 3 − ) is one of the main factors that induces nutritional deficiencies in plants, causing severe reductions in growth and productivity in vineyards (Covarrubias and Rombolà 2013;Cambrollé et al 2014;Murtaza et al 2017). In these soils, HCO 3 − concentrations may reach values over 15 mM.…”
Section: Introductionmentioning
confidence: 99%
“…In calcareous soils, characterized by alkaline or sub-alkaline pH, the presence of calcium carbonate (CaCO 3 ) and bicarbonate (HCO 3 − ) is one of the main factors that induces nutritional deficiencies in plants, causing severe reductions in growth and productivity in vineyards (Covarrubias and Rombolà 2013;Cambrollé et al 2014;Murtaza et al 2017). In these soils, HCO 3 − concentrations may reach values over 15 mM.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the application of amendments for soil improvement may contribute to nutrient use efficiency. Murtaza et al (2017) reported a significant variation in nitrogen use efficiency in saline-sodic soil in a rice-wheat cropping system. They found that the application of 100 kg N ha −1 with 50% soil gypsum requirement recorded the highest partial factor productivity; and that the application of 130 kg N ha −1 and 100% soil gypsum requirement had the highest agronomic use efficiency of nitrogen in both rice and wheat.…”
Section: Resource Use Efficiencymentioning
confidence: 99%
“…Studies have shown that soil salinization is essentially soil degradation, which will increase soil bulk density and electrical conductivity, and reduce soil permeability and water retention capacity [6][7] . On this basis, in order to improve this bad property, the current improvement methods are generally accepted to add desulfurization gypsum, biomass charcoal and fly ash to the saline-alkali soil [8][9][10][11] . relies mainly on water conservancy measures to control the saline-alkali land, but because of its inland location, fresh water resources are scarce.…”
Section: Introductionmentioning
confidence: 99%